Resistivity Signature of Graphene-Based Fiber-Reinforced Composite Subjected to Mechanical Loading - Liu, Hua; Deshmukh, Aparna; Salowitz, Nathan; Zhao, Jian; Sobolev, Konstantin (Frontiers in Materials, 2022)
The paper reports on a piezoresistivity response of fiber-reinforced cement mortar with graphene nano-platelets. The use of a small quantity (0.25% by the weight of cement) of nano-sized conductive particles of graphene turned conventional portland cement-based composite into a semiconductive stress-sensing material. The resistivity was measured using a surface resistivity tester, well accepted by the concrete industry, which employs an alternative current through four electrodes. Tension and compression tests of standard specimens were used to establish the relationship between the resistivity and the applied strain. Finite element analyses were employed to predict the resistivity of the slab specimen under three-point bending. The tests results and simulation indicate that the electrical resistivity of the graphene-cement composite material can be used for structural health monitoring and damage detection.